Development of Authentic Appraisal Instruments Basic Skills for Playing Football of Junior High School Students - Achmad Adib, Deni; Rusilowati, Ani; Hidayah, Taufik (Universitas Negeri Semarang, 2018)
Physical Education Sport and Health as one of the sports subjects has a sub-material practice of sports skills. Assessment of sports skills as performance assessment should also follow the assessment rules by BSNP. The objective of the study is to develop an authentic assessment instrument of the basic skills of playing football of junior high school students who qualify as valid, reliable and practical. The type of research is research and development following the Borg & Gall model. Technique of collecting data with documentation study, interview and observation. The result of the research is the assessment instrument product with lattice, observation sheet, rubric, and appraisal instrument. The result of instrument validity test with expert judgment show very valid that is 87,96%. Reliability test results with Cronbach's Alpha obtained coefficient of 0.931, and with Intraclass Correlation Coeficient (ICC) of 0.871 so that the developed instrument has a high degree of reliability. Practicality test results obtained 82% percentage so that the instrument has a high level of practicality.Ã‚Â© 2018UniversitasNegeri Semarang.